Policy Implementation Process in the Management of Tanjungpinang City Waste Bank to Realize the Blue Economy - Yudithia Yudithia; Akhyary Edy; Alfiandri Alfiandri; Kurnianingsih Fitri; Samin Rumzi; Subiyakto Rudi; Sentosa Ilham; Yafi Eiad (BIO Web of Conferences)
This research aims to analyze the implementation process of waste bank management policies in Tanjungpinang City by utilizing secondary data and triangulation analysis, based on Edward III’s policy implementation theory. The research method is qualitative, relying on secondary data collected from government reports, academic publications, policy documents, and statistical data. Triangulation is used to cross-verify the information, aligning it with Edward III’s theory, which includes four critical variables: bureaucratic structure, implementer disposition, resources, and communication. This approach allows for a comprehensive understanding of the factors influencing the effectiveness of policy implementation for waste management. The study identifies that efficiency and transparency in the bureaucratic structure, along with proactive behavior among implementers, are crucial for the success of the waste bank program. However, challenges such as a lack of public awareness and insufficient funding persist. The findings suggest that improving the competency of implementers, providing adequate infrastructure support, and enhancing communication between the government and the community are essential steps to overcoming these barriers. Therefore, this study not only provides an analysis of the current state but also offers practical recommendations to inform future policy adjustments and improve the waste management system in Tanjungpinang.